Attitude towards pharmaceutical promotional tools and its influence on physicians’ prescribing behaviour in Sudan - Eldrwish, M.A.; Aigbogun, Osaro; Kani, Y.; Sambasivan, M. (2022)
Purpose: Due to the proliferation of generic medicines, pharmaceutical marketing has become increasingly competitive, and marketing executives are now focusing their attention on understanding the prescribing behaviour of physicians to enable them to devise marketing strategies that would put them at a superior business position relative to their competitors. Previous studies carried out either lack a sound theoretical foundation, or report contrasting results, making generalizations sketchy. Thus, a better understanding of attitude-prescribing axiom is needed. Underpinned by the theory of reasoned action (TRA), this study aims to empirically examine the factors that predict the prescribing behaviour of physicians. Design/methodology/approach: A conceptual model was developed and tested on a sample of 355 respondents drawn from 76 private and 50 public hospitals in Sudan. The data set from the questionnaire survey included both general practitioners (N = 200) and specialists (N = 155). Primary data gathered were analysed using partial least squares structural equation modelling (PLS-SEM). Findings: The findings reveal that the prescribing behaviour of physicians is positively influenced by the physician’s attitude towards direct marketing, personal selling, educational travel and public relations, but negatively influenced by gifts. Besides, the moderating effect of subjective norms showed no significant influence on the relationship between attitude and prescribing behaviour. However, gender seems to moderate the attitude towards health sector-related charity on prescribing behaviour and the attitude towards scientific conferences on prescribing behaviour. Research limitations/implications: The findings gathered from this study offers a significant contribution to the ongoing debate on the essential factors that influence the prescribing behaviour of physicians in the hospital setting. Originality/value: By examining the essential factors that predict physicians’ prescribing behaviour, pharmaceutical companies can improve their understanding of physicians’ attitudes towards the pharmaceutical promotional tools. This is an aspect that is ill reflected in the literature.